Voces inocentes: violence and historical reality at El Salvador - Bedolla Villaseñor, Pastor (2023)
The article makes a review of a qualitative nature around the relationship between the childhood and the violence in the context of the civil war in El Salvador (1980-1992). The thought is instrumented by the exam of the Voces inocentes (2004) movie, which is conceived as a social production and as a representation of historical reality based on a prospective nature. This work emphasizes the film’s merit in its interest to make visible and denounce the responsibility of the primal supporters of the violence ‒currently unpunished‒ towards the Salvadorian childhood, whose psychosocial sequels established a Central American socio-historical environment configured by a humanitarian crisis started four decades ago at an unlucky ride “from the madness to hope”. This work uses the conceptual theoretical framework around the violence, developed by the Basque-Salvadorian Jesuit, Ignacio Ellacuría. Which conceived that the resulting violence can be assessed only from the initial criticism of the original violence of structural character